Web services – ICWS 2020 : 27th International Conference, held as part of the Services Conference Federation, SCF 2020, Honolulu, HI, USA, September 18-20, 2020, Proceedings /: 27th International Conference, held as part of the Services Conference Federation, SCF 2020, Honolulu, HI, USA, September 18-20, 2020, Proceedings. (2020) - Unknown
No abstract available